SOUL CARE CONCEPT FOR PERSON BASED ON THE PRESPECTIVE OF CHRISTIAN THEOLOGY - Lasatira, Frejhon Cleimen (DAS Institute, 2024)
The paradigm of self or person experiences significant differences. The influence of Platonic philosophy and also Gnosticism understands a person dichotomously. Apart from that, the Christian faith understands the self or person as a complete entity and identity where the spirit, soul and body unite and complement each other. By using a critical review of literature studies on Soul care, this research reveals firstly, the incarnation and ministry of Jesus and legitimizes the state of the three entities in the self or person as a complete and integrated identity. Second, the space of soul care covers all aspects of self or person in a small scope, as well as family and environment in a large scope. Third, the transformation of life on the pilgrimage of faith in and the practice of soul care depends on each person's choice.